Genital herpes on the penis and topic use of Uncaria Tomentosa: case report - Passos, Mauro Romero Leal (2022)
Introduction: genital herpes is an infectious sexually transmitted disease that affects people from different socioeconomic strata, it is widespread throughout the world and a frequent cause of painful genital lesions in men and women. Objective and Methods: to report a case of a patient with penile ulcers initially treated with various topical and oral products, who finally used Uncaria tomentosa gel topically. The final diagnosis was genital herpes. Results: The symptoms of pain and burning had rapid remission. The clinical course was satisfactory and after a week, the patient, with no lesion, reported having had sexual intercourse without discomfort and returned to professional activities. Conclusion: the topical use of Uncaria tomentosa gel 50 mg/g in penile ulcers was well tolerated, and showed no side effects with relief of local symptoms.